L’università che cade dalle nubi. Spazi e rappresentazioni della ricerca nel cinema italiano contemporaneo - Re, Valentina (Cinergie – Il Cinema e le altre Arti, 2013)
This article intends to analyze how the university environment is represented in Italian contemporary mainstream cinema, with the purpose of understanding how film and TV narratives can interact with other kind of discursive areas (such as press or politics) and affect and reflect the common perception of higher education. Based on Gérard Genette’s definition of “verisimilar” as something compliant with a system of maxims and values which are largely shared, I will show how, when it comes to the relationship between university and contemporary Italian cinema, there are three main phenomena we can point out. Firstly, the maxims tend to become stereotypes, with the result that the main issues addressed by the film are generalized and trivialized. Secondly, the absence of largely shared maxims allows for the wildest inventions and demonstrates a very little interest in the topics concerning higher education. Finally, as for the representation of the university spaces, we can observe that most films mechanically repeat the image of a pre-1968 university.